Chasing Cassandra [large type] - Kleypas, Lisa (Kleypas, Lisa. Ravenels., 2020)
"Everything has a price...Railway magnate Tom Severin is wealthy and powerful enough to satisfy any desire as soon as it arises. Anything--or anyone--is his for the asking. It should be simple to find the perfect wife--and from his first glimpse of Lady Cassandra Ravenel, he's determined to have her. But the beautiful and quick-witted Cassandra is equally determined to marry for love--the one thing he can't give. Everything except her... Severin is the most compelling and attractive man Cassandra has ever met, even if his heart is frozen. But she has no interest in living in the fast-paced world of a ruthless man who always plays to win. When a newfound enemy nearly destroys Cassandra's reputation, Severin seizes the opportunity he's been waiting for. As always, he gets what he wants--or does he? There's one lesson Tom Severin has yet to learn from his new bride: Never underestimate a Ravenel. The chase for Cassandra's hand may be over. But the chase for her heart has only just begun..."--Publisher.